Regulation of expression of venom toxins: silencing of prothrombin activator trocarin D by AG‐rich motifs. Issue 6 (16th March 2016) - Han, Summer Xia; Kwong, Shiyang; Ge, Ruowen; Kolatkar, Prasanna R.; Woods, Anthony E.; Blanchet, Guillaume; Kini, R. Manjunatha
ABSTRACT: Trocarin D (TroD), a venom prothrombin activator from Tropidechis carinatus, shares similar structure and function with blood coagulation factor Xa [ Tropidechis carinatus FX (TrFX) a]. Their distinct physiologic roles are due to their distinct expression patterns. The genes of TroD and TrFX are highly similar, except for promoter and intron 1, indicating that TroD has probably evolved by duplication of FX, the plasma counterpart. The promoter insertion in TroD accounts for the elevated but not venom gland‐specific expression. Here we examined the roles of 3 insertions and 2 deletions in intron 1 of TroD in the regulation of expression using luciferase as a reporter. By systematic deletions, we showed that a 209 bp region within the second insertion silences expression in mammalian and unmilked venom gland cells. Through bioinformatics analysis, we identified 5 AG‐rich motifs in this region. All except the 5th motif are important for silencing function. YY1, Sp3 and HMGB2 were identified to bind these AG‐rich motifs and silence gene expression in mammalian cells. Similar AG‐rich motif clusters are also found in other toxin genes but not in their physiologic counterparts. Thus, AG‐rich motifs contribute to regulation of expression of TroD, and probably other toxin genes.—Han, S. X., Kwong, S., Ge, R., Kolatkar, P. R., Woods, A. E., Blanchet, G., Kini, R. M. Regulation of expression of venom toxins: silencing of prothrombin activator trocarin D by AG‐rich motifs. FASEB J. 30, 2411–2425 (2016). www.fasebj.org